Exploratory study on the relationship between intellectual property and market valuation of Dow Jones Industrial Average (DJIA) component companies. - Lim, Genevieve Zai Wang. (2008)
This research sets out to investigate the relationship between the quantity of intellectual properties held by Dow Jones Industrial Average component companies and their market valuations.